Requirements change management - Fink, Laura (Dynamic relationships management journal, 2024)
The main theme of this article is the collection, preparation, and improvement of user requirements. The research relies on a case study of a complex ERP project from an international organisation. We proceed from the fact that the development of an individual ERP solution often goes beyond just a single project. Often, the development of the ERP solution continues even after the completion of the individual project. In particular, the article addresses the user requirements and their quality with regard to the requirements engineering process and change management. We discuss the characteristics of adaptive (e.g., agile) and predictive approaches, as well as how they affect the quality of user requirements. We emphasise that it is important for team members to be aware of the substantial impact that well-defined user requirements have on the success of the project. Although we argue that the number of change requests should not be taken as an indicator of project success, we discuss the factors that influence the number of changes during the project and the additional work after the project is completed. We identified two strategies that address the excessive number of requests for changes and additional work. The project team should give more attention to the preparation of high-quality requirements and, most of all, to enhancing their formalised testing and verification processes. Managing changes, especially changes in user requirements, is challenging and critical to project success. Companies should constantly optimise requirements analysis based on lessons learned from previous projects and ensure that past lessons are applied company-wide in future projects
Keywords: change management; enterprise system; ERP project success; requirements analysis; requirements engineering; user requirements